Characterization of Defects and Stress in Polycrystalline Silicon Thin Films on Glass Substrates by Raman Microscopy. (9th October 2011) - Kitahara, Kuninori; Ishii, Toshitomo; Suzuki, Junki; Bessyo, Takuro; Watanabe, Naoki
Abstract : Raman microscopy was applied to characterize polycrystalline silicon (poly-Si) on glass substrates for application as thin-film transistors (TFTs) integrated on electronic display panels. This study examines the crystallographic defects and stress in poly-Si films grown by industrial techniques: solid phase crystallization and excimer laser crystallization (ELC). To distinguish the effects of defects and stress on the optical-phonon mode of the Si–Si bond, a semiempirical analysis was performed. The analysis was compared with defect images obtained through electron microscopy and atomic force microscopy. It was found that the Raman intensity for the ELC film is remarkably enhanced by the hillocks and ridges located around grain boundaries, which indicates that Raman spectra mainly reflect the situation around grain boundaries. A combination of the hydrogenation of films and the observation of the Si-hydrogen local-vibration mode is useful to support the analysis on the defects. Raman microscopy is also effective for detecting the plasma-induced damage suffered during device processing and characterizing the performance of Si layer in TFTs.